Anti-Diabetic Effect of Spirulina and Karela in Streptozotocin Induced Diabetic Rats - Rahman, Md Mahbubur; Rahaman, Md Arifur; Akter, Nargis; Mahjabin, Mosfika; Ghosh, Munmun; Uddin, Md Jashim; Islam, Md Asraful (Journal of Comilla Medical College Teachers' Association, 2025)
Background: Diabetes mellitus (DM) is a significant public health issue affecting millions of individuals worldwide. Its macrovascular and microvascular complication are debilitating. Anti diabetic drugs available in the market have several common adverse effects and they also pose a financial burden to many diabetic patients. On the contrary the herbal alternatives might be a better option due to lack of such adverse effects, having other beneficial effects and are a cheaper choice of treatment. Objective: The study was undertaken to evaluate the anti-diabetic effect of Spirulina and aqueous extract of karela compairing with an oral antidiabetic drug glimepiride. Method: Total 35 healthy young albino rats of both genders were used for the experiment. Diabetes was induced by intraperitoneal injection of Streptozotocin@ 50mg/kg and experiment was carried out for a period of 3 weeks. Rats were divided into 5 groups and 7 rats on each. The groups were (i) Normal control (ii) Diabetic control which receives pellet as supplement (iii) Diabetic with oral administration of Spirulina (iv) Diabetic with oral administration of Karela (v) Diabetic with oral administration of Glimepiride. Result: The study showed that spirulina and karela reduces blood glucose level significantly compared to diabetic control group with the increases of body weight. Conclusion: The results of this study showed that oral administration of spirulina and extract of karela fruits may be a good alternative antidiabetic agent. J Com Med Col Teachers’ Asso Jan 2025; 29(1): 41-45